2016
DOI: 10.1002/joc.4755
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive stochastic assessment of meteorological drought indices

Abstract: Drought indices are among the most important tools used to monitor and detect drought around the world. Most of these indices have been experientially developed using data extracted from specific geographic locations and climatic conditions. Regarding the inherent complexity of drought phenomenon itself as well as local climatic conditions, there have been great uncertainties when using such indices to provide accurate and logical assessments of drought in different regions. Few stochastic assessment studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…It has been frequently used on time series of irregular hydrologic events to identify drought components and investigate their statistical properties [21], [22]. A -run‖ is defined as a portion of time series of the variable that is less than the chosen threshold [23], [24]. Following Nalbantis and Tsakiris [18], the drought event in this study is defined as the period where SDI values are less than the threshold value of zero.…”
Section: Drought Dentification and Drought Characteristicsmentioning
confidence: 99%
“…It has been frequently used on time series of irregular hydrologic events to identify drought components and investigate their statistical properties [21], [22]. A -run‖ is defined as a portion of time series of the variable that is less than the chosen threshold [23], [24]. Following Nalbantis and Tsakiris [18], the drought event in this study is defined as the period where SDI values are less than the threshold value of zero.…”
Section: Drought Dentification and Drought Characteristicsmentioning
confidence: 99%
“…This was consistent with previous studies [17,43,44], which indicated that considering more than one DI for drought studies can help investigate how well they cohere with each other and examine the sensitivity and accuracy of DIs. Montaseri and Amirataee [45] used seven meteorological drought indices to monitor drought characteristics in 12 diverse parts of the world endowed with various climatic conditions and found that the application of SPI can result in higher relative advantages to undertake a comprehensive and accurate analysis. Our study agrees with this study and also found SPI was the most reliable drought indicator among the DIs.…”
Section: Effectiveness Of Dis In Detecting Historical Droughtsmentioning
confidence: 99%
“…Bu indekslerden, meteorolojik kuraklığı tanımlamada sadece yağış değerlerini kullanan standartlaştırılmış yağış indeksi (SYİ) yöntemi dünyada sıklıkla kullanılır hale gelmiştir [6][7][8][9]. Dünya genelinde farklı kıtalardaki 10 ülkede bulunan toplam 12 bölgede gözlenmiş yağışla , farklı meteorolojik kuraklık indekslerini karşılaştırılmış ve bunlardan SYİ yönteminin diğer yöntemlere kıyasla meteorolojik kuraklığı tanılamakta daha tutarlı olduğu gösterilmiştir [7]. Polonya'da 2005 yılından itibaren, kuraklık izleme sistemlerinde 1, 2, 3, 6, 12, 24, 36 ve 48 aylık dönemlerdeki meteorolojik kuraklıklarının belirlenmesinde SYİ yönteminin etkin bir biçimde kullanıldığı belirlenmiştir [10].…”
Section: Introductionunclassified